FoxO and FoxM1 Transcription Factors Have Antagonistic Functions in Neonatal Cardiomyocyte Cell Cycle Withdrawal and IGF1 Gene Regulation - Sengupta, Arunima (2012)
RATIONALE: In the mammalian heart, cardiomyocytes withdraw from the cell cycle and initiate hypertrophic growth soon after birth, but the transcriptional regulatory mechanisms that control these neonatal transitions are not well-defined. OBJECTIVE: Forkhead family transcription factors have been implicated as positive (FoxM1) and negative (FoxO1 and FoxO3) regulators of cardiomyocyte proliferation prenatally, but their regulatory interactions and functions in neonatal cell cycle withdrawal have not been reported previously. Potential regulators of Fox activity, including the metabolic indicator AMP-activated protein kinase (AMPK), and Fox transcriptional targets (p21, p27, Insulin-like growth factor 1 (IGF1)) also were examined. METHODS AND RESULTS: In cultured neonatal rat cardiomyocytes, AMPK activates FoxOs, and AMPK inhibition is sufficient to induce cell proliferation. In vivo, combined loss of FoxO1 and FoxO3 specifically in cardiomyocytes leads to delayed cell cycle withdrawal and increased expression of IGF1 and FoxM1. Conversely, cardiomyocyte-specific loss of FoxM1 results in decreased neonatal cardiomyocyte cell proliferation, decreased expression of IGF1, and increased expression of cell cycle inhibitors p21 and p27. IGF1 is a direct downstream target of cardiac Fox transcription factors, which is negatively regulated by FoxOs and positively regulated by FoxM1, dependent on AMPK activation status. CONCLUSIONS: These data support a regulatory mechanism whereby the balance of FoxO and FoxM1 transcription factors integrates metabolic status, mediated by AMPK, and cell cycle regulation, through competitive regulation of target genes including IGF1, in neonatal cardiomyocytes.